Fillet Weight and Fillet Yield: New Metrics for the Management of Panfish and Other Consumption-Oriented Recreational Fisheries. (4th May 2017) - Lyons, John; Rypel, Andrew L.; Hansen, Jonathan F.; Rowe, David C.
Abstract: Proposals for regulations to improve panfish size structure often lack angler support, in part because of a perceived loss of panfish harvest. We propose that fillet weight and fillet yield, the percentage of the body weight available as fillets, are useful metrics for exploring regulation options and potential outcomes. We determined fillet weight and fillet yield for 321 Bluegill Lepomis macrochirus, 139 Black Crappie Pomoxis nigromaculatus, and 137 Yellow Perch Perca flavescens and developed equations to predict fillet weight from total length. Mean fillet yield was 29.5% for Bluegills, 28.6% for Black Crappies, and 33.1% for Yellow Perch. We used Bluegill size increases associated with a reduction in daily bag limits from 25 fish to 10 fish in seven Wisconsin lakes and then estimated fillet weights to compare the potential total weight of Bluegill fillets available to anglers under both a 10- and a 25-fish daily bag limit. We projected that many anglers might obtain a greater weight of Bluegill fillets per fishing trip under a 10-fish bag limit. We conclude that for consumption-oriented fisheries, fillet weight and fillet yield have value in demonstrating how more restrictive harvest regulations may sometimes lead to a greater weight of fillets for most anglers. Received April 19, 2016; accepted February 10, 2017 Published online April 11, 2017